Intra-articular kinetics of a cartilage targeting cationic PEGylated protein for applications in drug delivery. Issue 2 (February 2023) - He, T.; Zhang, C.; Colombani, T.; Bencherif, S.A.; Porter, R.M.; Bajpayee, A.G.
Summary: Objectives: Cartilage targeting cationic glycoprotein Avidin was PEGylated to synthesize a multi-arm Avidin (mAv) nano-construct with high drug loading content. Here we investigate mAv biodistribution and kinetics over a 7-day period following intra-articular (IA) administration in rat knee joints. Methods: Labeled mAv was injected into healthy rat knees, and joint tissues (articular cartilage, menisci, ligaments, tendons, fat pad) were harvested following sacrifice at 6 h, 1, 4 and 7 days. Its IA biodistribution and retention were measured using fluorescence microscopy. Tissue localization was compared in young vs old rats by immunohistochemistry. mAv chondrotoxicity and immune response were evaluated to determine safe carrier dose limits. Results: mAv penetrated through the full thickness of rat cartilage and other joint tissues within 6 h, remaining detectable within most joint tissues over 7 days. Intra-tissue uptake correlated strongly with tissue GAG concentration, confirming the dominant role of electrostatic interactions between positively charged mAv and the negatively charged aggrecan proteoglycans. mAv was uptaken by chondrocytes and also penetrated the osteocyte lacuno-canalicular system of peri-articular bone in both young and old rats. mAv did not cause cytotoxicity at concentrations up to 300 μM but elicited a dose dependent immunogenic response. Conclusions: mAv's ability to target a variety of joint tissues, chondrocytes, and peri-articular osteocytes without sequestration in synovial fluid makes it a versatile carrier for delivering a wide range of drugs for treating a broad class of musculoskeletal diseases. Drugs can be conjugated using simple aqueous based avidin-biotin reaction, supporting its clinical prospects.